#### Answer

$-183$

#### Work Step by Step

$S_{n}=\dfrac {a_{1}\left( r^{n}-1\right) }{r-1};a_{1}=\left( -3\right) ^{1}=-3;r=\left( -3\right) \Rightarrow \sum ^{5}_{i=1}\left( -3\right) ^{i}=\dfrac {-3\left( \left( -3\right) ^{5}-1\right) }{-3-1}=-183$

Published by
Pearson

ISBN 10:
013421742X

ISBN 13:
978-0-13421-742-0

$-183$

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.